Fiscal regimes in the EU - António Afonso; Priscilla Toffano (European Central Bank (ECB), 2013)
We assess the existence of fiscal regime shifts in the U.K., Germany, and Italy, using Markov switching fiscal rules. On the basis of a newly built quarterly data set, our results show the existence of fiscal regimes shifts, sometimes coupled with regime switches also regarding monetary developments. While in the UK “active” and “passive” (Leeper, 1991) fiscal regimes are somewhat clearer cut, in Germany fiscal regimes have been overall less active, supporting more fiscal sustainability. For Italy, a more passive fiscal behaviour is uncovered in the run-up to EMU.
Keywords: C22; E62; H62; 330; EU; fiscal regimes; Markov-switiching